Inferential and Critical Thinking Skills in Elementary Students - Anayanzin Antonio Cañongo; Guadalupe Acle Tomasini; Nelly Guadalupe Reyes López (Universidad Autónoma de Baja California, 2020)
One goal of education is to foster critical thinking skills in students. In this regard, the education system plays a key role, especially at early ages. The objective of this study was to determine levels of critical and inferential thinking skills in 6th-grade students. A cross-sectional exploratory study was designed with 33 students, comprising 16 boys and 17 girls (Mage= 11 years, sd = .24), who answered a questionnaire that presented a set of problems. Their answers were analyzed based on a rubric system used to assess their performance in terms of their analytical, evaluative, and argumentative skills. Two groups were formed: high-performing students and low-performing students. Statistically significant differences were found between them, with the high-performing group performing better both in inferential and critical thinking skills.